Unveiling the molecular mechanism of spiropyran-based receptors toward cyanide sensing: A theoretical study. (December 2022) - Lu, Jing; He, Chunliu; Hu, Yayun; Jia, Kangyu; Wang, Wenwen; Wang, Dong
Abstract: Spiropyran-based derivatives are widely used for highly selective colorimetric detection of cyanide ion. Herein, geometric structures, electronic characteristics, thermodynamics, density of states, frontier molecular orbital, and absorption properties for 2-(8-(hydroxymethyl)− 3', 3'-dimethyl-6-nitrospiro [chromene-2, 2'-indolin]− 1'-yl) ethanol (SP ), 2-(8-(hydroxymethyl)− 3', 3'-dimethyl-6-nitro-7-((4-nitrophenyl) diazenyl)− 4a, 8a-dihydrospiro [chromene-2, 2'-indolin]− 1'-yl) ethanol (SP-1 ), and the newly designed 2-(8-(hydroxymethyl)− 3', 3'-dimethyl-6-nitro-7-((4-nitrophenyl) diazenyl) − 4a, 8a-dihydrospiro [benzo[ b ][1, 4]oxazine-2, 2'-indolin]− 1'-yl) ethanol (SP-2 ) receptors are computed by density functional theory and time-dependent density functional theory, shedding light on their molecular mechanism toward cyanide sensing. The negative values of free-energy changes and the binding energies indicate that the CN - binding with the above-mentioned receptors is thermodynamically feasible. A sharp distinction in absorption wavelength is obtained after CN - binds to receptors, contributing to the sensitive detection of cyanide ion. Our results reveal that the difference in absorption wavelength is due to the configurational change and intramolecular charge transfer transition for receptor-CN - systems, in comparison with the π − π * transition for the receptors. This work could offer a clear theoretical guideline for fabricating high-performance probes (e.g., receptor SP-2/MC-2 ) toward cyanide. Graphical Abstract: ga1 Highlights: Disclosing the molecular mechanism of spiropyran-based receptors toward cyanide detection via theoretical calculations. Systematic analysis of geometric structures, electronic characteristics, thermodynamics, and adsorption properties. A clear theoretical guideline for fabricating high-performance fluorescent cyanide probes.